Evaluating monitoring methods for cetaceans. (September 2016) - Tyne, Julian A.; Loneragan, Neil R.; Johnston, David W.; Pollock, Kenneth H.; Williams, Rob; Bejder, Lars
Abstract: With increasing human pressures on wildlife comes a responsibility to monitor them effectively, particularly in an environment of declining research funds. Scarce funding resources compromise the level and efficacy of monitoring possible to detect trends in abundance, highlighting the priority for developing cost-effective programs. A systematic and rigorous sampling regime was developed to estimate abundance of a small, genetically isolated spinner dolphin ( Stenella longirostris ) population exposed to high levels of human activities. Five monitoring scenarios to detect trends in abundance were evaluated by varying sampling effort, precision, power, and sampling interval. Scenario 1 consisted of monthly surveys, each of 12 days, used to obtain the initial two consecutive annual abundance estimates. Scenarios 2, 3, and 4 consisted of a reduced effort, while Scenario 5 doubled the effort of Scenario 1. Scenarios with the greatest effort (1 and 5) produced the most precise abundance estimates (CV = 0.09). Using a CV = 0.09 and power of 80%, it would take 9 years to detect a 5% annual change in abundance compared with 12 years at a power of 95%. Under this best-case monitoring scenario, if the trend was a decline, the population would have decreased by 37% and 46%, respectively, prior to detection of a significant decline. With the potential of a large decline in a small population prior to detection, the lower power level should be used to trigger a management intervention. The approach presented here is applicable across taxa for which individuals can be identified, including terrestrial and aquatic mammals, birds, and reptiles.